Spatiotemporal control of transgene expression using an infrared laser in the crustacean Daphnia magna - Rina Shimizu; Joe Sakamoto; Nikko Adhitama; Mana Fujikawa; Pijar Religia; Yasuhiro Kamei; Hajime Watanabe; Yasuhiko Kato (Scientific Reports)
Abstract The crustacean Daphnia magna is an emerging model for ecological and toxicological genomics. However, the lack of methods for spatial and temporal control of gene expression has impaired the elucidation of molecular mechanisms underlying responses to environments in vivo. Here we report local activation of the hsp70 promoter-driven gene cassette in D. magna by the infrared laser-evoked gene operator (IR-LEGO), a method for heating the target cells with infrared irradiation. We identified the heat-inducible promoter upstream of the D. magna hsp70-A gene. Using this promoter, we generated a transgenic Daphnia harboring the heat-shock responsive GFP reporter gene and confirmed that the GFP gene responds to heat treatment not only in juveniles and adults but also in embryos. We collected embryos from the reporter line and irradiated four different regions of interest in the embryos: a proximal region of the third thoracic segment, a part of the midline, a second maxilla, and a distal region of the endopodite of the second antenna, all of which increased GFP fluorescence with an infrared laser. Our results suggest that the IR-LEGO method is useful for spatial and temporal control of gene expression and would advance the functional genomics in D. magna.